Organ sparing total marrow irradiation compared to total body irradiation prior to allogeneic stem cell transplantation. (24th June 2021) - Haraldsson, André; Wichert, Stina; Engström, Per E.; Lenhoff, Stig; Turkiewicz, Dominik; Warsi, Sarah; Engelholm, Silke; Bäck, Sven; Engellau, Jacob
Abstract: Objectives: Total body irradiation (TBI) is commonly used prior to hematopoietic stem cell transplantation (HSCT) in myeloablative conditioning regimens. However, TBI may be replaced by total marrow irradiation (TMI) at centres with access to Helical TomoTherapy, a modality that has the advantage of delivering intensity‐modulated radiotherapy to long targets such as the entire bone marrow compartment. Toxicity after organ sparing TMI prior to HSCT has not previously been reported compared to TBI or with regard to engraftment data. Methods: We conducted a prospective observational study on 37 patients that received organ sparing TMI prior to HSCT and compared this cohort to retrospective data on 33 patients that received TBI prior to HSCT. Results: The 1‐year graft‐versus‐host disease‐free, relapse‐free survival (GRFS) was 67.5% for all patients treated with TMI and 80.5% for patients with matched unrelated donor and treated with TMI, which was a significant difference from historical data on TBI patients with a hazard ratio of 0.45 ( P  = .03) and 0.24 ( P  < .01). Engraftment with a platelet count over 20 [K/µL] and 50 [K/µL] was significantly shorter for the TMI group, and neutrophil recovery was satisfactory in both treatment cohorts. There was generally a low occurrence of other treatment‐related toxicities. Conclusions: Despite small cohorts, some significant differences were found; TMI as part of the myeloablative conditioning yields a high 1‐year GRFS, fast and robust engraftment, and low occurrence of acute toxicity.